Discovery of non-electrophilic capsaicinoid-type TRPA1 ligands. Issue 5 (1st March 2015) - Del Prete, Danilo; Caprioglio, Diego; Appendino, Giovanni; Minassi, Alberto; Schiano-Moriello, Aniello; Di Marzo, Vincenzo; De Petrocellis, Luciano
Graphical abstract